The Concept of Revitalizing Traditional Institutions in the Criminal Law System to Realize Restorative Justice - Ismail, Dian Ekawaty; Mantali, Avelia Rahmah Y; Moha, Mohamad Rivaldi (Universitas Negeri Gorontalo, 2023)
This article examines data and facts related to implementing and functionalizing traditional institutions as living laws in society. It presents the concept of revitalizing traditional institutions in the criminal law system to realize restorative justice. According to indigenous peoples, justice is a complex concept because formal courts and other forums, such as customary courts, can administer it. This study aims to analyze the contribution of traditional institutions and restorative justice in the criminal law system in Indonesia. The approaches used in this research are conceptual, historical, statutory, and case approaches. The study results from show that customary institutions and restorative justice in Indonesia have been carried out through the participation of community members with traditional legal characteristics, cultural pluralism, moral values, and religion to solve problems through consultation to reach an agreement. Customary institutions and restorative justice in Indonesia are carried out by mediation for an agreement to reach an agreement in the best interests of victims, perpetrators, families, and other parties related to the traditional characteristics of law, cultural pluralism, moral values, and religion.